A Distinctive Analysis of Case Study, Action Research and Design Science Research - Dresch, Aline (2015)
Objective – This paper aims at analyzing the difference between research     methods that are typical in operations management (case study and action   research) with design science research. Design/methodology/approach – The paper adopts a theoretical-conceptual methodological approach, based on an extensive literature review. The literature review focused on studies that discuss the use of Case Study, Action Research and Design Science/Design Science Research. Theoretical framework – This paper reveals the foundations of Case Study and Action Research. Due to its recent use as a research method, Design Science Research is presented in greater depth. Findings – Firstly, we present design science and design science research as paradigms and as research methods, respectively, in the field of management. Secondly, we present the difference between Natural Sciences, Social Sciences and Design Science. Thirdly, we carry out comparative analysis of research methods Case Study, Action Research and Design Science Research. Finally, we offer a set of suggestions for future research regarding the use of research methods in management, in general, and in operations management, inparticular. Contributions – The main contributions of this paper focus on reflecting about research methods used in the management field. An important contribution is expanding the repertoire of research methods for understanding and using Design Science Research. The use of this method can contribute to reduce the distance between rigor and relevance, which has been described by several authors.